2009
DOI: 10.1177/1528083709102934
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Wrinkle Free Properties of Carboxymethylated Cotton Fabric via Ionic Crosslinking with Poly(vinylpyrrolidone)

Abstract: Incorporation of poly(vinylpyrrolidone) (PVP) in the structure of cotton, carboxymethylated cotton (CMC) or ionically crosslinked cotton fabric induces besides ether crosslinking of cotton cellulose, strong columbic forces and weaker forces such as dipole—dipole, hydrogen bonds, van der Waals, or hydrophobic interactions. The ether bonds are formed in the dry state (i.e., un-swelled state), whereas, the other interactions are formed in wet state (i.e., swelled state) of cotton fabrics. Both interactions greatl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The method was adopted from previous work. 10 Small pieces (2.5 × 2.5 cm) were cut from different parts of the treated sample. These pieces were further cut into smaller pieces (3 × 3 mm).…”
Section: Acid-base Titrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The method was adopted from previous work. 10 Small pieces (2.5 × 2.5 cm) were cut from different parts of the treated sample. These pieces were further cut into smaller pieces (3 × 3 mm).…”
Section: Acid-base Titrationmentioning
confidence: 99%
“…[6][7][8][9] In prior work, cotton fabric made anionic via carboxymethylation with monochloroacetic acid can be crosslinked in a second step by application of agents with the opposite ionic charges. 10 Hashem et al reported enhancing wrinkle free properties of carboxymethylated cotton fabric via ionic crosslinking with poly(vinylpyrrolidone). 11 In addition, layer-by-layer self-assembly deposition of polyelectrolytes on ionic cotton have been studied in recent reports.…”
Section: Introductionmentioning
confidence: 99%
“…DMDHEU is widely used to impart easycare and durable press properties to cotton apparel because it is cost effective and efficient. 17 However, DMDHEU produces free formaldehyde during application, which is considered probably to be carcinogenic, based on studies on animals which have revealed neoplastic lesions at the point of contact in the respiratory tract, although there is limited evidence of its carcinogenic effect on the human respiratory tract. 17,18 The results show that DMDHEU-treated cotton specimens contain small quantities (58 ppm) of free formaldehyde which can be toxic, allergenic and carcinogenic.…”
Section: Determination Of Formaldehydementioning
confidence: 99%
“…17 However, DMDHEU produces free formaldehyde during application, which is considered probably to be carcinogenic, based on studies on animals which have revealed neoplastic lesions at the point of contact in the respiratory tract, although there is limited evidence of its carcinogenic effect on the human respiratory tract. 17,18 The results show that DMDHEU-treated cotton specimens contain small quantities (58 ppm) of free formaldehyde which can be toxic, allergenic and carcinogenic. Extensive efforts have been made to find formaldehyde-free crosslinking agents to process cotton fabrics but numerous disadvantages such as high cost, inadequate reactivity, fabric yellowing, excessive fabric tendering, and toxicity were observed in all alternative agents.…”
Section: Determination Of Formaldehydementioning
confidence: 99%
See 1 more Smart Citation